The relationship between teachers' information technology integration self-efficacy and TPACK: A meta-analysis - Zeng, Youlai; Wang, Yue; Li, Shunyu (Frontiers in Psychology, 2022)
Using the method of meta-analysis, this study explored the relationship between teachers’ self-efficacy and TPACK in the context of educational information technology integration and focused on the moderating variables that affect the relationship. Through literature search, 28 independent effect sizes with 7777 subjects were obtained. Heterogeneity test illustrated that random effects model is appropriate. Funnel plot and Begg and Mazumdar’s rank correlation test found there was no publication bias in this meta-analysis. After effect size test, it followed that teachers’ information technology integration self-efficacy was significantly positively correlated with TPCK (r =0.607, P <0.001). The moderating effect test indicated that the relationship was moderated by the subjects’ career stages, but not by gender, teaching stages, disciplines and measurement tools.